Nurses' Knowledge and Attitudes toward Lesbians Seeking Perinatal Care in Israel. Issue 1 (2nd January 2021) - Tzur-Peled, Sharona; Sarid, Orly; Kushnir, Talma
ABSTRACT: In recent decades, there has been an increasing tendency among lesbians to realize their desire to become parents. Nurses provide perinatal care to lesbians at women's healthcare centres from the pregnancy planning stage until childbirth, serving as a source of information, advice and support. However, little is known about nurses' personal and professional characteristics, including knowledge and attitudes concerning perinatal care of lesbians at women's health centres. The current study was a cross sectional study that assessed a convenience sample of 184 nurses who provide perinatal care to lesbians at women's health centres belonging to the two largest health organizations in Israel. The average score received by participants on a homosexuality knowledge questionnaire was 10.4 on a scale of 0–17, indicating moderate levels of factual knowledge about homosexuality. Of all nurses surveyed, 83.2% had negative attitudes with regard to the treatment of lesbians. Nurses' personal and professional characteristics were found to be associated with these attitudes.